Usability factors that influence effectiveness of mobile learning management system (MLMS) for secondary schools in Malaysia - Hashim, A.S. (Institute of Electrical and Electronics Engineers Inc., 2017)
Usability is one of the important aspects that needs to be taken into consideration when designing a mobile learning management system (MLMS). This is to ensure the usefulness and easiness of the system to be operated by the users in conducting teaching and learning activities. Lacking in usability aspects have caused suffers to the users in using the system and it has also demotivated the users in performing educational activities through the system. Therefore, this paper presents the usability factors that influence the effectiveness of MLMS for secondary schools in Malaysia. Based on literature that has been conducted, two main aspects of usability were identified; device and mobile web usability. For device aspect, mobile web technology and Software as a Service (SaaS) of cloud computing were included as the factors while for mobile web usability aspect, three factors were incorporated including navigation, content and layout. Questionnaire instrument has been applied to validate those usability factors that can influence the effectiveness of MLMS. The questionnaire has been distributed to 257 secondary school students. Result of the study showed that all the usability factors that have been included are important to ensure the effectiveness of MLMS for secondary schools in Malaysia. © 2016 IEEE.